PENGEMBANGAN MODUL BERBENTUK KOMIK BERBASIS KONTEKSTUAL UNTUK PEMBELAJARAN MATEMATIKA DI SMA - Fadila Suciana (Jurnal Edukasi dan Penelitian Matematika, 2018)
Abstract Module was one of the learning materials in learning process. Learning materials held the position as first capital which will used and produce. However, learning materials which used in school was not contextual and motivate studens to use it, so developed module of comics based on contextual on linear equation system of three variables. Kind of this research was R&D with aimed to produce module which valid, practice, and effective. This research used ADDIE model consisting of the analysis, design, develop, implement, and evaluate. Instrumen of this research consisted of the questionnaires; analyze, validation, practicalities, and interview of sheet; and test which analyzed descriptively. Result shows that quality of module is very valid with construck aspect has module component, content arranged base on curriculum, language aspect appropiate to EBI and visual already good technically. Module is very practice because easy to use, can understanding, and saving time. Module is effective to improve result of studying is one of the learning materials in studying process.Keywords— module, comics, contextual, ADDIE, design.